Proposal for micromachined accelerometer, based on a contactless suspension with zero spring constant - Poletkin, Kirill V. (2012)
In this paper, a micromachined accelerometer, based on a contactless suspension with a zero spring constant which is a new challenge that provides possibility to significantly increasing accuracies of the micromachined inertial sensor is proposed. Minimization of the spring constant of the contactless suspension is achieved by combining inductive and electrical contactless suspensions. To study the conditions required to eliminate the spring constant of the suspension and achieve stable levitation of the accelerometer proof mass, a mathematical model of the suspension is developed. It is shown that such a suspension can be developed in principle.